2. MORTALITY RATE AND ASSOCIATED FACTORS IN PATIENTS WITH PULMONARY HYPERTENSION DUE TO LEFT-SIDED VALVULAR HEART DISEASE (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the mortality rate, 1-year survival rate, and related factors in patients with pulmonary hypertension due to left-sided valvular disease.Methods: A descriptive longitudinal cohort study (retrospective and prospective) was conducted on 146 patients aged ≥ 18 years with pulmonary artery systolic pressure > 45 mmHg and moderate or greater left-sided valvular lesions. The study was carried out at the Vietnam National Heart Institute, Bach Mai Hospital and Hanoi Medical University Hospital (4/2023-4/2025). Multivariate Cox regression was used to identify predictors of mortality.Results: The mortality rate during a mean follow-up of 161.6 days was 9.3%, a 1-year survival rate of 90.7%. Mean LVEF in the death group was 38.93 ± 15.89%, significantly lower than 53.83 ± 15.53% in the survival group (p = 0.001). Systolic pulmonary artery pressure (sPAP) > 60 mmHg (HR = 3.313; p = 0.031), NYHA class IV (HR = 6.092; p = 0.030), and reduced left ventricular ejection fraction (HR = 0.946; p = 0.002) are statistically significant factors associated with patient mortality. Left ventricular end-diastolic diameter (Dd) was inversely associated with mortality (HR = 0.919; 95% CI: 0.857-0.985; p = 0.017). Other variables such as age, sex, hypertension, diabetes, and pulmonary artery pressure were not statistically significant.Conclusion: Systolic pulmonary artery pressure, LVEF, and Dd are independent echocardiographic prognostic factors for mortality in patients with pulmonary hypertension due to left-sided valvular heart disease. The 1-year survival rate is 90.7%. Close monitoring of these parameters is essential in clinical management to improve treatment outcomes and prognosis.
Keywords: Pulmonary artery pressure; left heart valve disease; echocardiography.